Respiratory Schemes in the Class Edrioasteroidea - Bell, B. M. (Journal of Paleontology, 1977)
Edrioasteroids exhibit at least three major plans of thecal construction. Each suggests a different solution to the fundamental problem of respiration faced by all thecate echinoderms. Species of the order Edrioasterida employed the hydrovascular system as their primary respiratory device, a conventional echinoderm solution. A radial canal was suspended in the thecal cavity beneath the floorplates of each ambulacrum. Alternate lateral branches extended up into the ambulacral groove through vertical passageways which lie along sutures between contiguous floorplates. These branch canals ultimately terminated in podia and when the ambulacral coverplates opened, the podia functioned both as respiratory structures and food gathering devices. Species of the suborder Lebetodiscina (order Isorophida) also used external extensions of radial canals as their primary respiratory organs. But here lateral branch canals extended directly to the exterior of the theca, not into the ambulacral grooves. Lebetodiscinid coverplates extend laterally beyond the ends of the floorplates into the thecal cavity. Coverplate passageways lie along sutures between contiguous coverplates; these passageways open directly to the exterior of the theca. Lateral branch canals extended obliquely upward along the coverplate passageways to end as external podia. Thus, podial respiration could occur with the coverplates either open or closed. Species of the suborder Isorophina (order Isorophida) used anal respiration with exchange occurring in a cloacal chamber. No suggestions of ambulacral podia are found in these forms. The anal plates form a unique, complex, valvular structure. Expansion and contraction of various parts of the theca pumped water in and out of the cloacal chamber through the anal valve.
Keywords: paleontology